1986
DOI: 10.1111/j.1600-065x.1986.tb01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Immunoglobulin Class Switch Recombination

Abstract: The comparative analysis of Ig class switch recombination in a priori IgG/IgA-expressing myelomas and hybridomas, in switch variants and in activated normal B cells shows the following characteristics of class switch recombination in activated B cells: It is prevented during most of B cell ontogeny. It happens on both IgH loci of activated and switched B cells. The recombination is programmed in that on both IgH loci of switched cells the same switch regions recombine with Smu. This is true at least for the Ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 65 publications
0
33
0
Order By: Relevance
“…One possibility we consider envisions the Ighm/ c-myc exchange in a mature, class switch competent Bcell that has encountered antigen and other appropriate signals and prepares itself for isotype switching. In this situation, the initial lesion that provokes illegitimate recombination between Ighm and c-myc may be a DNA double-strand break in Sm due to internal rearrangements of Sm, mostly deletions and occasionally inversions, known to occur prior to class switching (Radbruch et al, 1986;Dunnick et al, 1989). The interruption of Sm may lead to Ighm/c-myc recombination and chromosomal translocation t(12;15) on the non-productive Igh allele, followed by deletional remodeling' of the t(12;15) by aberrant class switch recombination and normal class switching on the productive Igh allele (see Figure 7 for more details).…”
Section: Discussionmentioning
confidence: 99%
“…One possibility we consider envisions the Ighm/ c-myc exchange in a mature, class switch competent Bcell that has encountered antigen and other appropriate signals and prepares itself for isotype switching. In this situation, the initial lesion that provokes illegitimate recombination between Ighm and c-myc may be a DNA double-strand break in Sm due to internal rearrangements of Sm, mostly deletions and occasionally inversions, known to occur prior to class switching (Radbruch et al, 1986;Dunnick et al, 1989). The interruption of Sm may lead to Ighm/c-myc recombination and chromosomal translocation t(12;15) on the non-productive Igh allele, followed by deletional remodeling' of the t(12;15) by aberrant class switch recombination and normal class switching on the productive Igh allele (see Figure 7 for more details).…”
Section: Discussionmentioning
confidence: 99%
“…Conclusions Switch recombination in proliferating myeloma and hybridoma cells is usually less frequent than 10-/cell/generation (Radbruch et al, 1980;Radbruch, 1986). Upon activation of normal splenic B-cells, however, switch recombination occurs at frequencies of 100-101/cell/generation, and in >50% of the switched cells on both IgH loci (Coutinho and Fomi, 1982;Radbruch et al, 1986a). Class switch recombination is directed to mostly the same switch regions on the two chromosomes of a cell.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the 5Ј-C /cmyc exchanges were accompanied invariably by large deletions in S was consistent with this hypothesis, since S deletions are common in B cells undergoing isotype switching. 14,15 Furthermore, the average length of deletions in S was 2.7 kb and thus considerably longer than the average deletion in c-myc, which was just 171 bp (calculated from Table 2, last two columns). This suggested that S was targeted by a deletional mechanism (switch recombinase?)…”
Section: Mechanism Of the 5ј-c /C-myc Exchangementioning
confidence: 92%